What are the most effective person-centred interventions to manage people with dementia on acute wards that wander? A systematic review - Harbord, Nicholas (2012)
Background: The prevalence of dementia is steadily on the increase, and this trend is set to continue. Many people with dementia exhibit agitated behaviours; one particular manifestation of this agitation is wandering. Ideally agitation should be managed with the use of person-centred interventions; however there are reports that pharmacological management of agitation is commonplace, despite it not being recommended as a routine first line treatment. Study data for the effectiveness of non-pharmacological alternatives is currently lacking, particularly interventions that could be performed on busy acute medical wards. Furthermore evidence suggests that nursing staff are often not equipped with the knowledge to effectively manage the challenging behaviours. Standards of hospital care are failing to effectively meet the care needs of people with dementia. This systematic review aimed to improve the knowledge gap of frontline nursing staff on acute wards by synthesising the available evidence to form an evidence-based practice guideline that the staff can use to effectively manage people with dementia that wander. Review methods: A systematic search protocol was devised and then performed on a large range of databases, excluding studies before 2000, and studies in languages other than English. The Joanna Briggs Institute reviewer manual was used to guide the process. Data was extracted from the included studies using a data extraction tool and all studies were subjected to a rigorous critical appraisal. Results: 1957 initial search results were narrowed down to six studies which satisfied the inclusion and exclusion criteria: two examined alternative-therapy based interventions; two – moderate intensity physical exercise; and the remaining two individualised interventions. All 6 of the studies took place in the nursing home setting; therefore the applicability of the interventions to acute hospital wards could not be well judged. All of the interventions showed a degree of effectiveness at reducing various types of agitation including wandering; however 5 of the 6 studies were of poor quality, therefore it was not possible to make and confident recommendations for practice, based on this. Conclusions: The results show that there is a real need for more research into non-pharmacological interventions to manage wandering and agitation in general. More high quality studies are required, on larger study samples. Overall the review shows the potential that non-pharmacological interventions have to effectively manage wandering, however the practice recommendations have a low level of validity.